Dr. Serkan Sabancıoğullarından — Deep Plane Facelift — Istanbul - Sabancıoğullarından, Serkan (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Serkan Sabancıoğullarından, practicing in Istanbul, Turkey. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002942; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; turkey; istanbul